2021
DOI: 10.1101/2021.10.07.463536
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effector FEP3/IRON MAN1 modulates interaction between BRUTUS-LIKE1 and bHLH subgroup IVb and IVc proteins

Abstract: Plants use the micronutrient iron (Fe) efficiently to balance the requirements for Fe during growth with its potential cytotoxic effects. A cascade of basic helix-loop-helix (bHLH) transcription factors is initiated by bHLH proteins of the subgroups IVb and IVc. This induces more than 50 genes in higher plants that can be grouped in co-expression clusters. Gene co-expression networks contain information on functional protein interactomes. We conducted a targeted yeast two-hybrid screen with pairwise combinatio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 120 publications
0
3
0
Order By: Relevance
“…Under Fe-deficient conditions, IMA/FEP peptides compete with IVc subgroup bHLH TFs to interact with BTS/BTSL, thereby inhibiting the degradation of these TFs by BTS/BTSL. Therefore, this competition is essential for maintaining the Fe-deficiency response in Arabidopsis roots (Figure 1A) (Li et al, 2021;Lichtblau et al, 2022;Veĺez-Bermudez and Schmidt, 2022). Despite recent progress in this area, the original event that activates this signaling cascade in Fedeficiency response has not yet been identified and requires further examination.…”
Section: Introductionmentioning
confidence: 99%
“…Under Fe-deficient conditions, IMA/FEP peptides compete with IVc subgroup bHLH TFs to interact with BTS/BTSL, thereby inhibiting the degradation of these TFs by BTS/BTSL. Therefore, this competition is essential for maintaining the Fe-deficiency response in Arabidopsis roots (Figure 1A) (Li et al, 2021;Lichtblau et al, 2022;Veĺez-Bermudez and Schmidt, 2022). Despite recent progress in this area, the original event that activates this signaling cascade in Fedeficiency response has not yet been identified and requires further examination.…”
Section: Introductionmentioning
confidence: 99%
“…It was recently shown that IRON MAN (IMA) peptides interact with and are ubiquitinated by BTS, which inhibits the degradation of bHLH105 and bHLH115 through binding competition (Li et al, 2021). In the same line of evidence, the interaction of BTSL1 with PYE and bHLHs of the subgroup IVc is attenuated by the peptide IMA1 (Lichtblau et al, 2022). Interestingly, mutation applied to the Model for transcriptional regulation of Fe homeostasis.…”
Section: Transcriptional Regulationmentioning
confidence: 99%
“…Owing to their increased abundance upon Fe deficiency, IMA peptides compete with clade IVc bHLH proteins for binding to BTS, preventing their degradation and promote induction of downstream Fe deficiency responses (Figure 2) (Li et al, 2021). Interaction with IMA peptides, specifically IMA1/FEP3, has also been demonstrated for BTSL proteins (Lichtblau et al, 2022) OsIMA1 and OsIMA2 appear to function similar to Arabidopsis IMA/FEP peptides (Kobayashi et al, 2021). Overexpression of both homologs conferred Fe deficiency tolerance to rice plants and led to the accumulation of Fe in all tissues, including seeds.…”
Section: Ironman and Other Superheroes: Fe Sensing In Plantsmentioning
confidence: 99%